Changes in stool frequency following chicory inulin consumption, and effects on stool consistency, quality of life and composition of gut microbiota. (November 2019) - Watson, Anthony W.; Houghton, David; Avery, Peter J.; Stewart, Christopher; Vaughan, Elaine E.; Meyer, P. Diederick; de Bos Kuil, Minse J.J.; Weijs, Peter J.M.; Brandt, Kirsten
Abstract: Inulin is a soluble dietary fibre, also classified as a prebiotic, extracted from chicory roots. The present study aimed to determine the effect of consumption of native chicory inulin on the stool frequency of middle-aged to older adults (40–75 years old) with uncomfortably but not clinically relevant low stool frequency, specified as two to four days without bowel movements per week. Two randomised, double blind, placebo-controlled crossover trials were conducted using similar protocols in differing populations. Trial A was conducted in Amsterdam, The Netherlands and subsequently Trial B was conducted in Newcastle, United Kingdom. Both trials involved supplementation for 5 weeks with 10 g per day of inulin or placebo, a washout period of 2 weeks, and then crossed over to receive the other treatment. In Trial B, faecal gut microbiota composition was assessed using 16S rRNA gene sequencing. In Trial A, which 10 volunteers completed, the stool frequency was significantly increased to an average 4.9 ± 0.23 (SEM) times per week during inulin periods versus 3.6 ± 0.25 in the periods with placebo ( p  = 0.01). In contrast, in Trial B which 20 volunteers completed, there was no significant effect of the inulin on stool frequency (7.5 ± 2.1 times per week with inulin, 8.1 ± 3.0 with placebo, p  = 0.35). However, many subjects in Trial B had a stool frequency >5 per week also for the placebo period, in breach of the inclusion criteria. Combining the data of 16 low stool frequency subjects from Trials A and B showed a significant effect of inulin to increase stool frequency from 4.1 to 5.0 per week ( p  = 0.032). Regarding secondary outcomes, stool consistency was significantly softer with inulin treatment compared to placebo periods, it increased 0.29 on the Bristol stool scale ( p  = 0.008) when data from all subjects of Trials A and B were combined. No other differences in bowel habit parameters due to inulin consumption were significant. None of the differences in specific bacterial abundance, alpha or beta diversity were significant, however the trends were in directions consistent with published studies on other types of inulin. We conclude that 10 g per day of native chicory inulin can increase stool frequency in subjects with low stool frequency. Graphical abstract: Image 1 Highlights: Inulin as 10g day -1 for 5 weeks significantly increased stool frequency in 16 older volunteers compared with maltodextrin.. This increase was found in volunteers with low stool frequency (2 days or more per week without bowel movements). Directions of changes in secondary outcomes were generally consistent with expectations for prebiotic effects of inulin. Secondary outcomes included quality of life symptoms, stool consistency and composition of the faecal microbiota. Among secondary outcomes, only softening of stool consistency reached significance within the present study.